2014
DOI: 10.1523/jneurosci.1870-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Autophagosome Dynamics by Huntingtin and HAP1 Is Disrupted by Expression of Mutant Huntingtin, Leading to Defective Cargo Degradation

Abstract: Autophagy is an essential cellular pathway for degrading defective organelles and aggregated proteins. Defects in autophagy have been implicated in the neurodegenerative disorder Huntington's disease (HD), in which polyglutamine-expanded huntingtin (polyQ-htt) is predominantly cleared by autophagy. In neurons, autophagosomes form constitutively at the axon tip and undergo robust retrograde axonal transport toward the cell body, but the factors regulating autophagosome dynamics and autophagosome maturation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
314
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(344 citation statements)
references
References 63 publications
(8 reference statements)
20
314
0
Order By: Relevance
“…A defect in selective autophagic clearance of the ironbinding protein ferritin (ferritinophagy) with loss of HTT function in HD patients and mice may therefore reflect an impairment in ferritinophagy (13,44,45). Both mutant HTT expression and HTT knockdown are found to impair axonal trafficking of vesicles, mitochondria, and autophagosomes in neurons in vitro and in vivo (7)(8)(9)12), consistent with a loss of Atg11/Atg23-like membrane trafficking.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A defect in selective autophagic clearance of the ironbinding protein ferritin (ferritinophagy) with loss of HTT function in HD patients and mice may therefore reflect an impairment in ferritinophagy (13,44,45). Both mutant HTT expression and HTT knockdown are found to impair axonal trafficking of vesicles, mitochondria, and autophagosomes in neurons in vitro and in vivo (7)(8)(9)12), consistent with a loss of Atg11/Atg23-like membrane trafficking.…”
Section: Discussionmentioning
confidence: 96%
“…Loss of HTT in mouse cells reduces primary cilia formation, and deletion of HTT in ependymal cells leads to alteration of the cilia layer, suggesting a role for HTT in ciliogenesis (6). Mutant HTT expression and HTT knockdown have also been found to impair axonal trafficking of vesicles, mitochondria, and autophagosomes in neurons in vitro and in vivo (7)(8)(9). A clear molecular mechanism to relate these findings to the function of the HTT protein, however, has not yet emerged.…”
mentioning
confidence: 99%
“…ALS patients also exhibit increased levels of the autophagy initiation proteins beclin-1 and the Atg5-Atg12 complex (Hetz et al, 2009) and an overall increase in autophagosomes (Sasaki, 2011). In Huntington's disease models, autophagosome formation at the axon tip and density along the axon are not altered (Baldo et al, 2013;MartinezVicente et al, 2010;Wong and Holzbaur, 2014a).…”
Section: Autophagosome Biogenesis In Neuronsmentioning
confidence: 99%
“…Using live-cell imaging in cultured neurons, recent studies have found that autophagosomes that undergo axonal transport engulf both mutant SOD1 (Maday et al, 2012) and polyQ-htt (Wong and Holzbaur, 2014a), further demonstrating that autophagy contributes to protein turnover in the axon. Thus, autophagy might play a crucial role in regulating aggregate formation both at synapses and along the axon.…”
Section: Cargo Loading Of Disease-associated Proteinsmentioning
confidence: 99%
“…Dendritic release of secreted proteins (e.g., BDNF, NT-3, and NT-4) and diffusible molecules, such as nitric oxide, can transsynaptically regulate neurotransmitter release [43][44][45] . Injury of motoneuron projections to myocytes caused synaptic remodeling of inputs to motoneurons which was influenced by nitric oxide synthesis 46 .…”
Section: Discussionmentioning
confidence: 99%